Introductory overview of "The epididymis: present progress, future directions" (proceedings of the Fifth International Conference on the Epididymis) - Avellar, Maria Cristina W. (2011)
This Special Issue of the Journal of Andrology consists of the Proceedings of the Fifth International Conference on the Epididymis (Epididymis V), which took place October 25 to 28, 2010, in A´ guas de Sao Pedro, Sao Paulo, Brazil. Based upon the central theme Epididymis: Present Progress, Future Directions, peer-reviewed papers from 18 of the invited speakers are gathered herein. They provide a unique opportunity for reproductive biologists to become updated on the many recent discoveries and advances in epididymis structure and function. Here, we present meeting highlights and an introductory overview of the papers, organized by their main themes.